Pendidikan Bisnis, Bisnis Pendidikan - Sumargo, Bagus (Bina Nusantara University, 2004)
The implication of educations decentralization implies that colleges have authority to manage the whole education process. Nevertheless, the education have to be conducted professionally. The colleges should determine one study program havingÂ business oriented. Therefore, the education is driven into business purposes.